INTRA-OPERATIVE MAGNESIUM SULPHATE INFUSION DECREASES AGITATION AND PAIN IN PATIENTS UNDERGOING FUNCTIONAL ENDOSCOPIC SINUS SURGERY-A PROSPECTIVE, RANDOMIZED, CONTROLLED AND DOUBLE-BLINDED CLINICAL TRIAL - GUNTREDDY, AMAN SAI; NAIK, KORRA GOPA; GIRISH, BEHARA (International Journal of Current Pharmaceutical Research, 2023)
Objective: To assess the potential role of magnesium sulphate in the reduction of postoperative agitation and pain following functional endoscopic sinus surgery d in the ENT department. Methods: A prospective, randomized controlled double blinded clinical trial was carried out on 100 patients belonging to both sexes, aged between 18-55 y, posted for functional endoscopic sinus surgery (FESS) under general anaesthesia. Results: Intraoperative administration of magnesium sulphate in patients undergoing functional endoscopic sinus surgery decreases postoperative agitation and pain intensity; rescue analgesic consumption in the early postoperative period; and the length of stay in PACU. Conclusion: Intravenous Magnesium sulfate decreases patient agitation and pain after functional endoscopic sinus surgery.